Analysis of the Value of Cephalometric Parameters of the Face and Odontometric Parameters of the Jaws of the Dental Rows in Variable Bite - Glushko І. А. (Actual Dentistry, 2025)
Introduction: One of the main issues of orthodontics today is to solve the problem of optimizing the diagnosis of pathology of the dentofacial apparatus, improving methods for restoring intermaxillary relationships, and eliminating disproportions. The correlation of odontometric indicators and parameters of the apical bases of dental arches is the basis of biometric methods for studying plaster models of the jaws. The issues of studying the parameters of the dental arches of both patients’ jaws are relevant from a clinical and morphological point of view [1–3, 7, 8, 11, 14, 19]. The proportionality indices of Tonn, Gerlach, and Malyhin are used to determine the ratio of the upper and lower incisors in physiological occlusion, vertical disocclusion, and deep incisor overlap. The sizes of teeth and dental arches in individuals with physiological occlusion are determined depending on their gnathic and dental types. There is a relationship between the sizes of dental arches in the sagittal and transverse planes. The above indices determine the types of dental arches [4, 5, 8]. Currently, there are known classifications of the shape of dental arches with a detailed description of their basic linear indicators and methods for analyzing odontometric and craniometric parameters of the facial skull. Characteristics of the shapes and sizes of inferior dental arches, which are caused by partial tooth loss, have been studied. It has been noted that occlusion anomalies lead to changes in function due to a violation of the correspondence of the dental arches of the jaws [6, 9, 12]. At present, the odontometric parameters and linear parameters of the dental arches in patients with dolichognathic, brachygnathic, and mesognathic facial types with normodontia, macrodontia, and microdontia in the permanent occlusion period have been systematized in quite a detail [13]. Establishing an accurate diagnosis with a rational plan of orthodontic material prevents possible complications with the existing variability of the bones of the facial skull with different variants of their structure, various dentofacial anomalies, and peculiar proportions of the cerebral and facial skulls [12]. Domestic and foreign scientists, based on the presence of a correlation between the features of the sizes of the bone structures of the facial skull, identify the personalized features of each patient [5, 6, 13]. At the same time, information regarding the key points of cephalometric facial dimensions and odontometric indicators of jaws with different facial types is quite controversial. The existing methods for diagnosing dental arch pathology currently require clarification and addition, which is explained, firstly, by the emergence of modern research methods; secondly, by the development and implementation of new technologies in the treatment of occlusal disorders; thirdly, by the increased demands of patients for therapeutic, preventive and diagnostic measures. Most methods for studying the sizes of dental arches and determining the correspondence of tooth sizes to the parameters of dental arches are based on measuring individual teeth and or groups of teeth and the subsequent correlation with the proposed dental and interdental indices and coefficients. Methods for assessing the transverse and sagittal linear dimensions of dental arches (Pont, Linder, and Harth; Korkhaus methods) are based on this principle. Given the differences in index values when assessing the specified methods (Pont and Linder-Harth), difficulties often arise in interpreting the study results. In addition, it is not specified for which variants of the shape of dental arches these methods are recommended for use in clinical orthodontic practice. Modern classifications of the shape and size of dental arches are supported by information about the main linear dimensions; however, they are given in the study of patients with physiological occlusion of permanent teeth. The proposed methods for measuring the diagonal dimensions of dental arches are based on the position of the interdental point, which can change its position in case of anomalies in the shape and size of dental arches. That is why optimizing methods for determining the shape and size of dental arches, considering the individual characteristics of the maxillofacial region within the framework of modern orthodontic diagnostics, requires a more in-depth and detailed study to improve diagnostic and therapeutic measures.